2018
DOI: 10.1038/s41467-018-03342-5
|View full text |Cite
|
Sign up to set email alerts
|

Strong selection during the last millennium for African ancestry in the admixed population of Madagascar

Abstract: While admixed populations offer a unique opportunity to detect selection, the admixture in most of the studied populations occurred too recently to produce conclusive signals. By contrast, Malagasy populations originate from admixture between Asian and African populations that occurred ~27 generations ago, providing power to detect selection. We analyze local ancestry across the genomes of 700 Malagasy and identify a strong signal of recent positive selection, with an estimated selection coefficient >0.2. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 45 publications
5
68
0
1
Order By: Relevance
“…The Duffy-null rs2814778 (C) allele disrupts an erythroid transcription factor GATA-1 binding site in the promoter of ACKR1 and as a result, the erythrocytes of homozygote rs2814778 carriers do not express ACKR1 protein 54 . Erythrocytes lacking this Duffy antigen are refractory to the malaria parasite Plasmodium vivax infection and hence the Duffynull variant confers an evolutionary advantage 55 . Recent experimental work in mice has shown that ACKR1 deficiencies during early haematopoiesis do not result in reduced production of neutrophils, rather neutrophils exhibit altered phenotypic characteristics that result in their preferential loss from blood by egress into tissues, particularly via migration to the spleen, thus causing neutropenia 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The Duffy-null rs2814778 (C) allele disrupts an erythroid transcription factor GATA-1 binding site in the promoter of ACKR1 and as a result, the erythrocytes of homozygote rs2814778 carriers do not express ACKR1 protein 54 . Erythrocytes lacking this Duffy antigen are refractory to the malaria parasite Plasmodium vivax infection and hence the Duffynull variant confers an evolutionary advantage 55 . Recent experimental work in mice has shown that ACKR1 deficiencies during early haematopoiesis do not result in reduced production of neutrophils, rather neutrophils exhibit altered phenotypic characteristics that result in their preferential loss from blood by egress into tissues, particularly via migration to the spleen, thus causing neutropenia 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The ELAI analysis detected the regions with significantly high amounts of Asian-and Papuan-related ancestries in the Munda genomes. These regions were considered to have been shaped by natural selection based on the principles that have been used to detect "adaptive introgression" of genes in admixed populations 10,11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the following genetic characteristics of Munda population using the genome-wide single nucleotide polymorphism (SNP) data: genetic relationship between Munda and other Oceanian populations, a sign of the admixture in Munda genomes, and signals of positive selection based on the excess of either Asian-related or Papuan-related ancestry observed in specific genomic regions of Munda. To assess the positive selection (i.e., the effect of admixture on the adaptation of Munda population), we performed a genome-wide analysis of local ancestry of Munda individuals using the Efficient Local Ancestry Inference (ELAI) algorithm 10 , which was recently applied for the detection of potential selection signals in the genomes of Malagasy, an AN-speaking population in Madagascar who have AN-related and Bantu-related genetic ancestries 11 . Our results revealed that: (1) the Munda people were genetically related to other populations from the Solomon Islands, (2) the Munda genomes consisted of both Asian-and Papuan-related ancestry components, and (3) the significant amounts of Asian-and Papuan-related ancestries were observed in the region containing the annexin A1 (ANXA1) gene and in the HLA class II region, respectively.…”
mentioning
confidence: 99%
“…Along the west African coast, the transatlantic slave trade impacted the demographic history of numerous populations, for example, the population history of Cape Verdean Kriolu speakers . The Indian Ocean slave trade network, along the east African coast, mainly impacted African islands from southeastern Africa, for example, the genetic landscape of the Malagasy population …”
Section: New Insights To Study Past and Recent History In Africamentioning
confidence: 99%
“…The IndianOcean slave trade network, along the east African coast, mainly impacted African islands from southeastern Africa, for example, the genetic landscape of the Malagasy population 32,33. 4 | ENGAGEMENT OF GENOMIC RESEARCH IN AFRICA…”
mentioning
confidence: 99%